Political Views on Gender Relations Among Women in Health Careers and Their Partners - Wuri Handayani; Jen Salafian; Ita Mutiara Dewi; Fikri Disyacitta (Universitas Negeri Semarang, 2025)
This study aims to understand how career women working as health personnel at Puskesmas Gondokusuman I perceive gender equality in their relationships with partners, particularly in light of their dual roles as public workers and domestic managers. Despite an era promising formal equality, women still face structural inequalities in household relations, particularly concerning role distribution, decision-making, and childcare. A qualitative descriptive approach, employing phenomenological methods, was used, involving in-depth interviews and focus group discussions with female health workers. The findings suggest that the concept of gender equality is dynamic and contextual, varying according to negotiated values, personal experiences, and inherited cultural norms. Although informants demonstrated agency and critical reflection on traditional roles, daily life practices still reveal a double burden and subtle power relations. These findings are analysed using gender constructivism theory, Foucault's theory of power relations, and Butler's gender performativity, affirming that equality is not a static condition but a result of continuously negotiated social interactions. The study recommends strengthening family based equality policies and transforming gender relations values through education and cultural narrative reform.